The Development of Diabetic Foot Ulcer Prevention Model Based on Psychosocial Perspectives, Attitude, Intention, Coping Mechanisms (Indian Journal of Public Health Research & Development, 2020)
Context: Objective: Foot ulcer is one of the diabetic complications that causes death in the world. Preventivebehavior can be used to prevent diabetic foot ulcers. Therefore, this study aims at developing a modelof diabetic foot ulcer prevention based on psychosocial, attitude, intention and coping mechanisms. Thestudy used a cross-sectional study design to look at the relationship between variables using simple randomsampling in 329 respondents, ages 18-85 years, who made an inspection visit at a health care center. Theresearch instrument consisted of psychosocial variables namely knowledge and stress, attitude, intention,coping mechanisms, and foot ulcer prevention . Furthermore, the data were analyzed using SEM-PLSsoftware. Results shows most of the respondents were in the youth category ages 18 - 65 years. Analysis ofshows that there is a psychosocial influence on attitude T = 10,92, there is an effect of attitude on intentionT = 2,43, there is an influence of intention on coping mechanisms T = 8,28, there is an influence of intentionon Foot ulcer prevention T = 2,57, there is an influence of coping mechanisms on foot injury preventionT = 5,02. Knowledge, stress, attitude, intention and coping mechanisms contribute to prevent diabetesfoot injuries. The Conclusions Knowledge, stress and attitude variables contributed the most indirectly todiabetes foot injury prevention. Contributions are directly affected by coping mechanisms and intentions.
Keywords: Psychosocial, Attitude, Intention, Coping Mechanisms, ulcer